Kaanduri and other stories - Dāśa Benhura (Orient Blackswan Private Limited, 2015)
Do not come down, oh rain! -- The apartment -- Arrogance -- The blankets are really warm! -- The book review -- Clouds -- Freedom fifty saloon -- God's creation -- Gold -- Gurudakshina -- The harmonium -- Kaanduri -- Rebati -- Responsibility -- Sukanti's house -- The bicycle -- The noose -- The picture -- The rickshaw-wallah